A critique of using machine intelligence for e-decision-making - Auda, Gasser (2004)
This paper is a critique of Artificial Intelligent agents used in the hearts of e-planning and e decision making systems in general.It refers to a case study of a web site that teaches JAVA programming language and is designed as a multi-level curriculum, each level with specific curricular objectives designed for users with certain background knowledge.The Instructor, to be replaced with the Intelligent Expert System, decides on the student’s level based on his/her answer to a detailed questionnaire.The paper critically compares the Instructor’s performance to three systematic approaches - procedural programs, logic expert systems, and neural networks.